Gaya Hidup dan Hipertensi Pada Lanjut Usia di Kecamatan Kasihan Bantul Yogyakarta - Edi Sampurno Ridwan; Esti Nurwanti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2014)
Life style plays important role toward emerging chronic diseases including hypertension. This is an observationanalytical research using cross-sectional design. It was 100 respondents in the research obtained using Slovin formula from 9887 population. Stratiﬁed random sampling and simple random sampling were assigned to select sample. Variables were measured with FFQ (food frequency questionnaire), International Physical Activity Questionnaire, and Smoking Questioner. Data was analyzed using Chi-Square and the result was junk food consumption leading to 4 times risk for hypertension (OR, 4,083). In addition, sedentary behavior (p 0.004) and smoking (p 0.001) were signiﬁcant factors to lead hypertension for older people. Conclusion, junk food, sedentary behavior, and smoking habits can be the risk factors of hypertension. Thus, it is imperative to develop health promotion program focusing on the changing life style for aged group.